Efeito de diferentes programas de treinamento de força em mulheres na pós-menopausa: alterações na composição corporal, capacidade físico-funcional e marcadores inflamatórios - CARNEIRO, Marcelo Augusto da Silva (2019)
The purpose of this first study was investigate effect of cluster-set training with higher load (CST-HL) or lower load (CST-LL) compared to traditional sets resistance training (TSRT) on muscle performance (muscle mass, strength, power and rate of force- and power- development) in postmenopausal women (PW). Each leg of 23 PW was randomly allocated into three groups: TSRT (n = 12 legs), CST-HL (n = 14 legs) and CST-LL (n = 14). TSRT and CST-HL performed three sets of four repetitions at 90% one repetition maximum (1RM), 3s per muscle action, with a 1.5-min rest interval between sets. CST-LL performed three sets of six repetitions at 40% 1RM (as fast and strongly as possible) with a 1.5-min rest interval between sets. Only CST-HL and CST-LL groups performed 30s interrepetition rest periods. All groups training twice-weekly during 8 weeks. All groups increase thigh muscle mass, maximal muscle strength, peak and mean power, peak and mean angular velocity and dynamic rate of power development, without difference between them. CST-LL was superior to TSRT and CST-HL for improving isometric RFD at 0–30, 0–50, 0–100 and 0–200ms. This study showed that TSRT, CST-HL and CST-LL are similarly effective at improving muscle performance (except to isometric RFD) in PW. Particularly, CST-LL is superior to TSRT and CST-HL in increasing isometric RFD (≤ 200ms) in PW. About to the second study less is known about the impact of lower-load resistance training (LL) on inflammatory biomarkers, body adiposity, and physical function. This study tested whether LL is an alternative strategy for improving inflammatory biomarkers, visceral adiposity, muscle mass and physical function in PW when compared with higher-load resistance training (HL). Moreover, we tested whether changes in inflammatory biomarkers are associated with alterations in body composition and muscular function. This study included 29 PW: LL (n = 14, 30-35 repetitions) and HL (n = 15, 8-12 repetitions). LL and HL were performed three times per week, during 12 weeks. Body composition was measured using DXA, maximal muscle strength by 1RM and physical function by sit-to-stand test, timed-up and go, gait speed at 4 meters, 400 meters (400-m) and six-minute walk test (6MWT). The blood indicators were measured by ELISA. There were no differences between the groups in the changes of adiposity, 1RM, physical function (short tests), cytokines, and adipokines. However, greater magnitude of increase in leg lean body mass was observed in LL. Greater magnitudes of increase in 6MWT and of decrease in 400M were observed in HL. There was a superiority of HL over LL in increasing logHO-1. Moreover, the LL decreased HSP70/72. These results suggest that LL is an alternative strategy to improve inflammatory biomarkers, body adiposity, maximal muscle strength and physical function (short tests) in PW. Moreover, eHSP70 and HO-1 may be used as biomarkers to track changes in muscle mass and physical function.